The Influence of Patriarchic Culture on Pregnancy: A Case on Farming Households in Rural - Rosnah; Syaifudin Suhri Kasim (International Journal of Qualitative Research, 2022)
This study is intended to describe the influence of patriarchal culture during the pregnancy of the mother, especially in rural farming households. This study uses a qualitative descriptive method in the context of the "Phenomenology" paradigm. Determination of informants is done intentionally. Research informants consisted of mothers who have children, pregnant women and their husbands, and medical officers (midwives). Primary data sources were obtained directly through interviews with informants and the results of field observations. Data collection is done through (a) direct interviews and (b) observation. Data validation was carried out by triangulation to determine the accuracy of the method used and the accuracy of the data obtained. The results showed that in poor households in rural areas the influence of patriarchal culture during the mother's pregnancy can be seen in (1) Domestic activities in which men are still in important control of the household. In this activity, pregnant women are treated like non-pregnant mothers, as they continue to do household chores until it is close to the time to give birth. (2) Public activities, pregnant women are still directly involved in land or garden cleaning. (3) The husband's trust in taboo matters about eating, especially for pregnant women, so that pregnant women lack nutritional intake. (4) The attitude of the husband towards the mother's pregnancy, in which they consider that the mother's pregnancy is a natural thing and becomes the mother's own business. (5) Husband's support for pregnant women to carry out pregnancy care is still very lacking.